Building a New Ocean Literacy Approach Based on a Simulated Dive in a Submarine: A Multisensory Workshop to Bring the Deep Sea Closer to People - Salazar, Janire; Dominguez-Carrió, Carlos; Gili, Josep-Maria; Ambroso, Stefano; Grinyó, Jordi; Vendrell-Simón, Begoña (Frontiers in Marine Science, 2019)
The deep sea is considered the largest environment on Earth, providing multiple ecosystem services to human societies. Although its relevance has long been recognized, not enough attention and interest is generally given to it by society, and its study is almost non-existent in formal and informal education. Getting the deep sea closer to the general public would considerably benefit from the commitment of scientists involved in deep-sea research, who could generate effective educational tools based on their own personal experiences in research projects. Here we report the development of an immersive workshop that displays video footage and sounds recorded during scientific dives inside a replica of a submarine. The workshop recreates with as much detail as possible the experience of researchers when exploring the deep sea using modern technologies, in this case a manned submersible. The workshop is conducted by scientists from the same research team which carried out the study, aiming to transmit their expertise and personal experience to participants. The workshop is complemented with additional spaces that allow the exchange of knowledge and ideas between scientists and the general public. It also shows other, more intrusive, sampling methodologies traditionally used to prospect and study the deep sea, putting them in contrast with modern techniques, more respectful with the environment. Since its first exhibition in 2010, the workshop has been displayed at over 50 events held in different locations around Spain, including educational fairs, museums, schools and fishermen associations. Over 6000 participants have taken part in the activity, most of which have expressed their opinions and suggestions about the workshop by voluntarily filling a specific survey, and thus helping to improve it. They also stated which aspects of the deep-sea life were unknown to them. Thanks to its versatility and to its simple operation, this educational workshop opens a wide range of possibilities to significantly improve the current knowledge on marine life (and deep-sea ecosystems in particular) by the general public, also aiming to reduce the distance between academia and citizenship.